2020
DOI: 10.1111/tct.13298
|View full text |Cite
|
Sign up to set email alerts
|

Can Balint groups fill a gap in medical curricula?

Abstract: Background: Emotions play a fundamental role in the professional development of doctors. Teaching medical students about the role of emotions in illness and relationships with patients can be challenging. Balint groups involve a case presentation and discussion focussed on the emotional component of patient interactions. This study aimed to assess whether a Balint group helped medical students to gain a better understanding of the role of emotions in the doctor-patient relationship, and whether students believ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Of 18 studies included, six were from United States [ 22 , 23 , 24 , 25 , 26 , 27 ], three from United Kingdom [ 28 , 29 , 30 ], three from Australia [ 31 , 32 , 33 ], two from France [ 34 , 35 ], two from Taiwan [ 36 , 37 ], one from Germany [ 38 ] and one from Ireland [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of 18 studies included, six were from United States [ 22 , 23 , 24 , 25 , 26 , 27 ], three from United Kingdom [ 28 , 29 , 30 ], three from Australia [ 31 , 32 , 33 ], two from France [ 34 , 35 ], two from Taiwan [ 36 , 37 ], one from Germany [ 38 ] and one from Ireland [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gajree also identified that Balint groups improved the empathetic ability of students towards patients. 1 I believe the adapted groups I have described could therefore also enhance empathy towards students from a minority background, who suffer injustices that their white peers do not experience.…”
mentioning
confidence: 90%
“…Making space for ethnic minorities in student Balint groups I enjoyed reading Gajree's article on the benefits of Balint groups for medical students. 1 Although Balint groups traditionally focus on emotions around consultations with patients rather than a student's experience with their peers, 2 I feel such groups could be adapted to shift to also facilitating discussions around the experiences of medical students, as well as patients, from a diverse range of ethnic minority backgrounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Balint groups, six to eight colleagues reflect on their experiences and emotional aspects of their work. Balint groups are led by a professional, e. g. a psychotherapist [ 14 ]. Complementary to these types of collegial consultation, numerous models for reflection have been published, e.g., Schön (reflective-practice concept) [ 15 ], Johns (model for structured reflection) [ 16 ] or Korthagen (ALACT-model) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%